Lack of dermal penetration of topically applied gentamicin as pharmacokinetic evidence indicating insufficient efficacy. (2nd August 2018) - Oesterreicher, Zoe; Lackner, Edith; Jäger, Walter; Höferl, Martina; Zeitlinger, Markus
Abstract: Background: Treatment of skin and superficial soft tissue infections with topically applied antibiotics is a controversial topic, because only few clinical studies exist and target site concentrations after topical treatment are widely unknown. Objectives: This study aimed to investigate the target site concentration of topically applied gentamicin as a potential cause of therapeutic failure and to explore if microporation by laser might be used to improve penetration of gentamicin through the skin barrier. Methods: Six healthy volunteers were included in this cross-over Phase 1 study. On two study days, separated by a washout period, microdialysate and plasma sampling was performed for 6 h after administration of 500 mg of gentamicin cream on a predefined area. On one of the study days the skin was microporated before drug application using the P.L.E.A.S.E. Professional laser system. Results: In intact skin, C max and AUC values were 3.3 ± 5.64 ng/mL and 5.4 ± 10.4 ng·h/mL, respectively; thereby far under the threshold needed to treat common pathogens. With a C max of 474.2 ± 555.3 ng/mL laser application showed a significant increase in tissue penetration and decrease in pharmacokinetic variability; however, even after microporation no therapeutically active concentrations were achieved as indicated by C max /epidemiological cut-off ratios of 0.237 and 0.059 for Staphylococcus aureus and Pseudomonas aeruginosa, respectively. Solely after administration on microporated skin, plasma concentrations of gentamicin were quantifiable (lower limit of quantification 10 pg/mL). Conclusions: This study confirmed that after topical administration gentamicin penetration through the dermal barrier is insufficient, providing pharmacokinetic evidence that topical gentamicin in its current form might be inappropriate to treat skin infections.